(untitled) (European Journal of Natural Sciences and Medicine, 2020)
Chitin and chitosan are natural biopolymers that are included in the novel families of biological macromolecules. Chitosan its the main derivative of chitin, and research upon the characteristics and properties of these molecules has become increasingly evident and important. It was reported that the main and potential applications of these polymers as well as their derivatives are more than 200. These applications include biomedicine, pharmacy, agriculture, biotechnology, cosmetics. In the last years, especially in the pharmaceutical and medical fields chitosan has received considerable attentions as a functional, renewable, nontoxic and biodegradable biopolymer for diverse applications. The recent efforts of the scientists concentrated on the methods of preparation of chitin from raw material, on processing chitosan, as well as on the chemical and biological properties that help increase solubility in aqueous solutions.